2020
DOI: 10.1042/cs20200023
|View full text |Cite
|
Sign up to set email alerts
|

From animal models to patients: the role of placental microRNAs, miR-210, miR-126, and miR-148a/152 in preeclampsia

Abstract: Placental microRNAs (miRNAs) regulate the placental transcriptome and play a pathological role in preeclampsia (PE), a hypertensive disorder of pregnancy. Three PE rodent model studies explored the role of placental miRNAs, miR-210, miR-126, and miR-148/152 respectively, by examining expression of the miRNAs, their inducers, and potential gene targets. This review evaluates the role of miR-210, miR-126, and miR-148/152 in PE by comparing findings from the three rodent model studies with in vitro studies, other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 267 publications
0
25
0
Order By: Relevance
“…MiR-126 influences the VEGF pathway through inhibition of Spred1 and lower levels of placental miR-126 in PE were associated with decreased VEGF placental expression [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-126 influences the VEGF pathway through inhibition of Spred1 and lower levels of placental miR-126 in PE were associated with decreased VEGF placental expression [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…RNA enriched for small RNAs (including miRNAs) was isolated using the mirVana Paris Kit (Thermo Fisher). Reverse transcription and pre-amplification were performed using TaqMan miRNA primers (Thermo Fisher) and multiplex qPCR was done in a CFX96 thermal cycler (Bio-Rad) [ 25 ]. Raw C q values were calculated in Bio-Rad CFX manager software v.3.1 using automatic baseline and threshold settings.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, studies on early‐onset PE have gradually deepened into the molecular mechanism, and the role of miRNA in PE cannot be ignored 18, 25 . However, the pathway of action of miRNA is still unclear, so we studied the role of miR‐126 and VCAM‐1 in EOPE placental tissues and trophoblast cells, providing the possibility to elucidate the pathogenesis and treatment of EOPE.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have indicated that miR‐126 can regulate the expression of VCAM‐1 in lung cancer, gestational diabetes mellitus, atherosclerosis, and other diseases 15–17 . Previous studies have found that miR‐126 and VCAM‐1 are respectively involved in the occurrence and development of PE, 18–20 however, there is no report on the correlation between miR‐126 and VCAM‐1 in PE. In this study, we detected the expression of miR‐126 and VCAM‐1 in placental tissue and trophoblast to explore the role of miR‐126 and VCAM‐1 in the pathogenesis of early‐onset PE.…”
Section: Introductionmentioning
confidence: 99%
“…[35,36] Another three preeclampsia rodent model studies show elevated miR-210 in part driven by HIF-1α and NF-κBp50, induced by hypoxia and/or immune-mediated processes may contribute in preeclampsia by inhibiting anti-inflammatory Th2-cytokines. [37] miRNA125b as Biomarker Third Trimester of Pregnancy Hypertensive Disorder miR-125b in pregnant women can be detected from several different sites, the plasma from the mother, where it is often called the maternal circulating miR-125b and the placental cells, where it is called as placental miR-125b. [38][39][40] Circulating miR-125b supposedly comes from the placenta itself, as one in vivo study suggests, making the maternal circulating miR-125b and placental miR-125 closely related to one another.…”
Section: Methodsmentioning
confidence: 99%